ChemInform Abstract: Base and Solvent Mediated Decomposition of Tosylhydrazones: Highly Selective Synthesis of N‐Alkyl Substituted Hydrazones, Dialkylidenehydrazines, and Oximes. Issue 41 (19th September 2013) - Sha, Qiang; Wei, Yunyang
Abstract Base‐ and solvent‐controlled decomposition pathways of tosylhydrazones are explored.